2021
DOI: 10.1038/s41598-021-01440-x
|View full text |Cite
|
Sign up to set email alerts
|

Addition of daratumumab to multiple myeloma backbone regimens significantly improves clinical outcomes: a systematic review and meta-analysis of randomised controlled trials

Abstract: Daratumumab has shown clinical benefit in multiple myeloma. We aimed to evaluate the safety and efficacy of adding daratumumab to backbone anti-myeloma treatments. Systematic search was performed up to August 2021 to identify randomised controlled trials comparing the outcomes of backbone therapy with and without daratumumab in relapsed/refractory and newly diagnosed myeloma (RRMM and NDMM, respectively). Odds ratios (ORs) and hazard ratios (HRs) were calculated with 95% confidence intervals (CIs). Primary out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 40 publications
0
5
0
1
Order By: Relevance
“…In a comparison of the three medications, daratumumab emerged as the medication with the highest utilization and reimbursement. This can be attributed to the superior efficacy of daratumumab compared with ixazomib and elotuzumab [ 17 ]. Daratumumab can be used for either newly diagnosed or relapsed MM patients.…”
Section: Discussionmentioning
confidence: 99%
“…In a comparison of the three medications, daratumumab emerged as the medication with the highest utilization and reimbursement. This can be attributed to the superior efficacy of daratumumab compared with ixazomib and elotuzumab [ 17 ]. Daratumumab can be used for either newly diagnosed or relapsed MM patients.…”
Section: Discussionmentioning
confidence: 99%
“…The results demonstrated that the daratumumab-containing regimens daratumumab, lenalidomide, and dexamethasone (D-Rd) and D-Vd were more effective in improving PFS when compared with other evaluated regimens. In a recent NMA by Kiss et al [ 25 ], better clinical outcomes were demonstrated in patients with RRMM treated with daratumumab-containing vs control regimens with regards to minimal residual disease negativity, stringent complete response, death, and disease progression. Additionally, in an NMA by Luo et al [ 26 ], which synthesized results from 24 randomized controlled trials, it was demonstrated that D-Rd showed better efficacy than the other regimens with regards to nonresponse rate, time to progression, and PFS.…”
Section: Discussionmentioning
confidence: 99%
“…A klinikai vizsgálatok alapján a legígéretesebb túlélési eredményeket az RVd-protokoll CD38-ellenes monoklonális antitesttel (daratumumab, isatuximab) való kiegészítésével érhetjük el. Fontos azonban megjegyezni, hogy a kvadruplet terápia a hematológiai toxicitás és az infekciók gyakoriságának növekedésével jár [23][24][25].…”
Section: Transzplantációra Alkalmas Beteg Kezeléseunclassified